2011
DOI: 10.1016/j.vaccine.2011.04.044
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-dependent protective immunity elicited by adenovirus 5 expressing the surface antigen 1 from Toxoplasma gondii is mediated by CD8+ T lymphocytes

Abstract: Toxoplasma gondii is an intracellular parasite widely spread around the world. The Surface Antigens (SAG) 1, 2 and 3 are the main proteins expressed on the surface of T. gondii tachyzoites. Replication-defective adenovirus serotype 5 (rAd5) is one of the most potent recombinant viral vectors for eliciting T cell-mediated immunity in mice and humans. Here we show that vaccination with rAd5 expressing SAG1 (AdSAG1), but neither SAG2 nor SAG3, induces protective immunity in the highly susceptible C57BL/6 mice cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
1
13
0
1
Order By: Relevance
“…Secretion of parasite antigens into the host cell is known to be important for presentation via the MHC class I pathway, which samples the host cytosol and stimulates CD8 T cell responses to intracellular pathogens. This is in line with evidence that secretion into the host cell promotes recognition by CD8 T cells (31) and the fact that all of the T. gondii CD8 epitopes identified to date are derived from secreted parasite proteins (4,16,40,62). On the other hand, the impact of secretion on MHC class II presentation of potential parasite antigens is less clear, since both secreted and nonsecreted parasite antigens should have ready access to the class II MHC pathway via phagocytosis of intact parasites and debris.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Secretion of parasite antigens into the host cell is known to be important for presentation via the MHC class I pathway, which samples the host cytosol and stimulates CD8 T cell responses to intracellular pathogens. This is in line with evidence that secretion into the host cell promotes recognition by CD8 T cells (31) and the fact that all of the T. gondii CD8 epitopes identified to date are derived from secreted parasite proteins (4,16,40,62). On the other hand, the impact of secretion on MHC class II presentation of potential parasite antigens is less clear, since both secreted and nonsecreted parasite antigens should have ready access to the class II MHC pathway via phagocytosis of intact parasites and debris.…”
Section: Discussionsupporting
confidence: 69%
“…This approach has been used to examine CD8 T cell responses to T. gondii, leading to the identification of a number of endogenous CD8 antigens (4,7,16,40,62). Most strikingly, mice possessing the MHC-I molecule L d mount an immunodominant response to the HF10 decapeptide derived from the T. gondii protein GRA6 (4).…”
mentioning
confidence: 99%
“…In a similar manner, other authors have confirmed that SAG2A protein can be used for diagnostic procedures, and also include this protein as a target in the development of subunit vaccines against T. gondii infection [58]. However, strategies involving SAG2A as an immunogen yield divergent results, and some failed to protect susceptible mice from lethal infections [59-61]. Based on our results, we believe that the inability to establish SAG2A as an immunogen in those studies may be due to the modulatory properties of its C-terminal end and we suggest that r SAG2A ∆135 should be tested in those experimental models.…”
Section: Discussionmentioning
confidence: 95%
“…The same vaccine was able to reduce acute mortality and reduce cyst formation in C57BL/6 mice after challenge with ME49 strain. Protection was correlated with the capacity of AdSAG1 in activating CD8 + T cellmediated responses, in a mechanism dependent of MyD88 innate signaling and IL-12 production [44].We are now addressing the improvement of the vaccination strategy to enhance the levels of protection. In that sense, one of the major limitations for the viral vectored vaccines is the existence of anti-vector immunity, because it can reduce the efficiency of the immunization [61].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, these three viruses were used in homologous primeboost protocols, providing a significant level of protection against the chronic form of the disease in a model of toxoplasmosis in which BALB/c were challenged with the P-Br strain of the parasite [43]. However, in a different model where C57BL/6 mice were challenged with the ME49 strain, only the adenovirus encoding the SAG1 antigen showed protective properties [44]. This observation prompted us to focus our investigations in SAG1.…”
Section: Introductionmentioning
confidence: 99%